2005
DOI: 10.1177/1534735405282212
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Walking Poles on Shoulder Function in Breast Cancer Survivors

Abstract: Breast cancer treatment often results in impaired shoulder function, in particular, decrements in muscular endurance and range of motion, which may lead to decreased quality of life. The purpose of this investigation was to determine the effects of walking pole use on shoulder function in female breast cancer survivors. Participants had previously been treated with 1 or a combination of the following: mastectomy, breast conservation therapy, axillary lymph node dissection, chemotherapy, or radiation. Participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 17 publications
1
49
0
3
Order By: Relevance
“…All of authors dealing with rehabilitation issues [20][21][22][23][24][25][26][27][28][29] underline the necessity of doing additional research. However, it seems that current scientific evidence, especially in the areas of cardiology [21-23, 28, 29], confirm the usefulness of NW in the rehabilitation programmes of patients after acute coronary syndrome, with intermittent claudication, with coronary artery disease, and after myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All of authors dealing with rehabilitation issues [20][21][22][23][24][25][26][27][28][29] underline the necessity of doing additional research. However, it seems that current scientific evidence, especially in the areas of cardiology [21-23, 28, 29], confirm the usefulness of NW in the rehabilitation programmes of patients after acute coronary syndrome, with intermittent claudication, with coronary artery disease, and after myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…there were three papers that met the inclusion criteria. [3,[9][10][11][12][13][14][15][16][17][18][19], ten papers were on the use of NW in rehabilitation [20][21][22][23][24][25][26][27][28][29] and three items concerned biomechanical aspects of NW [2,30,31]. One publication was a case study of NW used for treating of a sacral stress fracture that resulted from training overload [32].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is some evidence it might provide additional benefits over normal walking by reducing joint loading 17,18 and increasing aerobic endurance 19,20 and muscular strength. 21 Furthermore, a handful of studies in breast cancer populations have concluded that Nordic walking can improve shoulder function 21,22 and does not increase the risk of lymphedema. 21,23 A literature search of major relevant databases (MEDLINE, PsycIN-FO, SportDiscus, and CINAHL) from 1960 to 2012 revealed no prior research testing Nordic walking in women with AIAA, and thus, it was concluded that it would be useful and important to conduct a preliminary study to test the study design and whether an intervention could be delivered as intended.…”
Section: Introductionmentioning
confidence: 99%